Caracterização da pulverização de mistura de tanque com diferentes pontas de jato plano - Jesus, Marcella Guerreiro de [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The evolution of methods of food production is setting new parameters on the final product quality. Thus, awareness programs grow increasingly which allows the new information to reach at the production field. This study aimed to analyze the interactions between fungicides and adjuvants in tank mixes, using different types of spray nozzles. The test was conducted with 15 treatments, consisting of two fungicides, an insecticide and adjuvants based on mineral oil, vegetable oil and surfactant. We used the tips jet plane (XR), air induction (AIXR) and jet impact (TT) plan. The addition of adjuvants in test solutions followed the patterns indicating the manufacturers of pesticides (addition or not of oil in the syrups), along with fiel d practices used by farmers, represented by the partial or total replacement of oil - based adjuvant surfactants. To determine the interference of adjuvants in spray mixes, there were four analysis: spectral of droplets, surface tension, viscosity and measur ing the length of the liquid film formed at the exit orifice of the spray nozzles. The readings of the droplet spectrum were using particle analyzer equipment in real time (laser diffraction); the evaluation of surface tension used the gravimetric method ( drop weight); the viscosity was analyzed in rotary viscometer and the evaluation of the size of the liquid film was performed by image analysis. The average results for each evaluation were compared using the confidence interval for the differences betwee n the ratings, at 95% probability (95% CI). The results demonstrated an increase in the DMV and reducing the percentage of less than 100 microns with the addition of surfactant adjuvants based on partial substitute for oil in treatments engeo Full drops, w hile the behavior was reversed in test solutions with Fox fungicides and Aproach Press. This inversion should be observed from the point of view of the different ...

A evolução do s métodos de produção de alimentos vem estabelecendo novos parâmetros na qualidade final do produto. Assim sendo programas de conscientização crescem cada vez mais para que se possibilite que as novas informações cheguem ao campo de produção. O presente trabalho teve como objetivo analisar as interações entre os produtos fitossanitários e os adjuvantes em misturas de tanque, utilizando diferentes tipos de pontas de pulverização. O ensaio foi conduzido com 15 tratamentos, constituídos de dois fungicidas, um inseticida e adjuvantes à base de óleo mineral, óleo vegetal e surfactante. Utilizou - se as pontas de jato plano ( XR), com indução de ar (AIXR) e de jato plano de impacto (TT). A adição de adjuvantes nas caldas seguiu os padrões de indicação dos fabricantes dos defensivos agrícolas (adição ou não de óleo nas caldas) , juntamente com as práticas de campo utilizadas pelos agricultores , representadas pela substituição parcial ou total dos óleos por adjuvantes a base de surfatantes . Para determinação da interferência dos adjuvantes nas caldas, realizaram - se quatro análises : espectro de gotas, tensão superficial, viscos idade e medição do comprimento dos filmes de líquido formados na saída do orifício das pontas da pulverização . As leituras de espectro de gotas foram realizadas por meio do equipamento analisador de partículas em tempo real (difração de laser) ; na avaliaçã o de tensão superficial utilizou - se o método gravimétrico (peso da gota); a viscosidade foi analisada em viscosímetro rotativo e a avaliação do tamanho do filme líquido foi realizada por análise de imagens . As médias dos resultados obtidos em cada avaliaçã o foram comparadas pelo Intervalo de Confiança para Diferenças entre as Médias, no nível de 95% de probabilidade (IC95%) . Os resultados mostraram ...
Keywords: Produtos quimicos agricolas - Adjuvantes; Defensivos vegetais - Tecnologia de aplicação; Pulverização; Agricultural chemicals